Interactive system for measurement of cervical and lumbar spine from digital radiographs - Bai, Zhong Yang (2010)
The objective of this project is to develop an interactive system capable of measuring cervical and lumbar vertebral body and disc heights, the Cobb angle as well as sagittal plane displacements that can be used for clinical analysis. Although X-ray imaging technology provides a non-invasive and accurate diagnosis of spine injuries and the data acquired from the radiographs can be useful, the images require interpretation by trained personnel. And the process of manual measurements can be time consuming. Therefore, an interactive system is needed to aid radiologists and/or surgeons in handling the large volumes of X-ray images.